Implementing Education for Democracy in Finnish Teacher Education - Fornaciari, Aleksi; Rautiainen, Matti; Hiljanen, Mikko; Tallavaara, Riitta (Schools (Chicago, Ill.), 2023)
Teacher education (TE) in Finland is based on strong university autonomy, including the right to decide the curriculum content and the teaching methods. Democracy and its values are generally seen as central principles for TE, and the normative basis for education promoting democratic culture is strong. However, in practice, education for democracy is not at the core of TE. On the contrary, building a culture of democracy and action with students is unsystematic and dependent on individual teachers.To overcome this challenge, we studied a group of 18 first-year teacher students focused on democracy education. The study suggests that with systematic education toward a strong conceptualization of "teachers as democratic/societal agents," TE can promote a teacher who sets being an active and societally participative democratic individual as their primary objective. This study also shows that democratic education requires long-term education, not just single courses.